The Emergence of Modern Design Discourse in the Eastern Mediterranean Region (EMR) - Saad, Qassim (Cumulus the Global Association of Art and Design Education and Research. Aalto University, School of Arts, Design and Architecture, 2021)
This study will offer an overview of applied discourses of design in the Eastern Mediterranean Region (EMR), including Egypt, Palestine, Lebanon, Syria, Jordan, and Iraq. These countries have been known for their pioneering statues, creative engagements, and influence on shaping, resourcing, and sustaining the emergent project of modernity in the region since the 1940s. Studies of the contemporary discourse of design for these countries are acknowledged as underdeveloped, with extremely limited studies addressing its context and practices. This study will survey identical phases throughout the contemporary history of these countries, observing major stages that transformed the societies within them into sovereign territories and national states after World War II. The study will explore and critically review key historical themes in the regional socio-political rhetoric since the 1950s, specifically those associated with and involved in shaping the emergence of design as a modern discourse in the region.